Impact of Pasteurization Process on the Quality and Marination Properties of Onion Juice - Kaya, Zehra; Ünlütürk, Sevcan; Yıldız, Mustafa Kemal; Demir, Hande; Unluturk, Sevcan; Becerikli, İsmail (My University, 2020)
This study aims to compare UV-C irradiation and conventional heat treatment to produce pasteurizedonion juice used as a meat marinating agent. The process conditions maximizing the inactivation oftarget microorganism Escherichia coli K-12 were; 0.5 mm sample depth, 30 min irradiation, 7.5mW/cm2 UV incident intensity for UV-C and, 74.5°C and 12 min for heat treatment. Except pH andnon-enzymatic browning index, differences between physicochemical properties of raw, UV-C andheat-treated onion juices were significant. Springiness and chewiness of unmarinated beefsteakswere higher compared to the ones marinated with the fresh and pasteurized onion juice (UV-C andheat). Pasteurization of onion juice (UV-C and heat) did not significantly affect general liking scorescompared to beefsteaks marinated in untreated onion juice.
Keywords: Gıda Bilimi ve Teknolojisi